Preparation of pyridine-3,4-diols, their crystal packing and their use as precursors for palladium-catalyzed cross-coupling reactions - Lechel, Tilman; Brüdgam, Irene; Reissig, Hans-Ulrich (Beilstein Journal of Organic Chemistry, 2010)
A series of trifluoromethyl-substituted 3-alkoxypyridinol derivatives has been deprotected to furnish pyridine-3,4-diol derivatives in good yields. The X-ray crystal structure analysis proved that a 1:1 mixture of pyridine-3,4-diols and their pyridin-4-one tautomers exist in the solid state. Subsequent conversion into bis(perfluoroalkanesulfonate)s were smoothly achieved. The obtained compounds were used as substrates for palladium-catalyzed coupling reactions. Fluorescence measurements of the biscoupled products showed a maximum of emission in the violet region of the spectrum.
Keywords: bisnonaflates; fluorescence; palladium catalysis; pyridine-3,4-diols; pyridines